Obesity, rather than high fat diet, exacerbates the outcome of influenza virus infection in influenza-sensitized mice - Guo, Weimin; Wu, Dayong; Li, Lijun; Ding, Samuel; Meydani, Simin Nikbin (Frontiers in Nutrition, 2022)
Introduction: Obesity is associated with impaired immune function and increased susceptibility to infection. High fat (HF) diet-induced obesity is a commonly used animal model. However, HF diet itself is known to affect immune function and infection. Thus, it is not discernable which one, HF diet or adiposity, is the major contributor to the observed impairment in immunity and susceptibility to infection in HF diet-induced obesity. We hypothesized that obesity is a major contributor to impaired immune function. Method and Results: Weight-matched outbred female CD-1 mice (1-mo) were randomly assigned to either a HF (45%) or a low fat (LF, 10%) diet group. Ten wk after feeding their respective diets, weight gain in the mice fed the HF diet varied greatly. Thus, based on the average body weight, mice in HF diet group were divided into two sub-groups: HF lean (HF-L) and HF obese (HF-O). After 25-wk, mice were immunized with an influenza A/Puerto Rico/8/34 vaccine and boosted 3-wk later. Five wk after the booster, mice were infected with influenza A/Puerto Rico/8/34 virus, and body weight was recorded daily for one month. HF-O mice exhibited significant weight loss after influenza virus challenge compared to LF and HF-L mice while LF and HF-L mice largely maintained their weight to a similar extent. Conclusion: Our findings suggest that obesity, rather than HF diet, per se, exacerbates the severity of influenza virus infection in influenza vaccinated mice.